Eksplorasi Kesadaran Siswa Melalui Program Bersih Lingkungan dalam Pengelolaan Sampah di SMP IT Khairunnas Kota Bengkulu - Randi Oktarian Putra; Muhammad Ilham Gilang; Ismail Ismail (Simpati, 2026)
This research is motivated by the low level of awareness among some students regarding maintaining a clean school environment and proper waste management. SMP IT Khairunnas,Bengkulu City, implemented a clean environment program as an effort to build students'environmental awareness through cleaning activities, waste sorting, and environmental management.school actively. This study aims to analyze the process of the environmental cleanup program in exploring students' awareness of waste management, identifying supporting and inhibiting factors of the program, and explaining the impact of the program on students' daily behavior in maintaining a clean school environment. This study uses a qualitative approach with fieldresearch. Data collection techniques were carried out through observation, interviews, and documentation. The primary data sources in this study were the principal, teachers, and students of SMP IT Khairunnas, Bengkulu City.Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. Data validity was carried out through technical triangulation and source triangulation. The results of the study indicate that the environmental cleanup program at SMP IT Khairunnas, Bengkulu City was implemented through class duty activities, mutual cooperation, sorting organic and inorganic waste, waste banks, and environmental education activities.